Social media marketing influence on Boutique Hotel customers’ purchase intention in Malaysia - Anshul Garg; Jeetesh Kumar (Tourism & Management Studies)
As of January 2020, global social media users have exceeded 3.8 billion, accounting for 49% of the world’s total population. Internet and social media have become an indispensable part of people’s daily lives worldwide. However, most previous research only focuses on social media marketing in other businesses, and there is less research about the development of boutique hotel social media marketing. This study investigates the relationship between different social media marketing practices and customers’ purchase intention in Malaysia’s boutique hotels. The article also explores how to properly conduct social media marketing to increase the customer purchase intention of boutique hotels and promote the boutique hotels’ development in Malaysia. The non-probability random sampling technique 309 response was collected from Malaysian social media users using an online survey. Findings of the research found out that factors including marketing activities and eWOM significantly impact customer purchase intention of the boutique hotels in Malaysia through the mediating variable perceived usefulness and the mediating variable perceived trust. The study offers implications for the development of social media marketing in boutique hotels.